Meningkatkan Kemampuan Siswa dalam Menemukan Ide Pokok Paragraf Melalui Pendekatan Saintifik di Kelas VI SD Negeri 1 Bumi Harjo: Improving Students' Ability in Finding the Main Idea of Paragraphs Through a Scientific Approach in Class VI SD Negeri 1 Bumi Harjo - Supanti, Supanti (Anterior Jurnal, 2022)
The purpose of this study is to find out: 1. A scientific approach can improve students' ability to find the main idea of a paragraph in Class VI Semester 1 of the 2019/2020 Academic Year of SD Negeri 1 Bumi Harjo. 2. Using a scientific approach can improve students' ability to find the main idea of a paragraph in Class VI Semester 1 of the 2019/2020 Academic Year at SD Negeri 1 Bumi Harjo. Research Methods: This research was conducted at SDN 1 Bumi Harjo with 26 students as the subject. The procedure of this research is through planning, action, observation, and reflection. The technique of collecting data is through tests, observations, and documentation, while the data is analyzed through data reduction, data display, and data consolidation.